Increasing Growth and Yield of Peanuts with Various Types and Dosages of Organic Fertilizer in Dry Land - Marlina Marlina; Neni - Marlina; Harniatun Iswarini; Dali Dali; A. Haitami; Khodijah Khodijah; Muhammad Hendra Saputra Wijaya; Haperidah Nunihlawati; Sutarmo Iskandar; Sasua Hustati Syachroni (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Dry land is very potential to be developed into agricultural land, one of which is planting peanuts, although it has constraints such as low pH and low soil fertility. Efforts can be made to improve soil fertility by applying organic fertilizer. Organic fertilizers are expected to improve the soil's physical, chemical, and biological properties and provide nutrients that peanut plants need. This research aims to obtain the right organic fertilizer type and dosage to increase peanut production. This research was conducted in farmers' fields in Margo Bhakti Village, Block C unit II, Mesuji District, Ogan Komering Ilir Regency (OKI) from March to June 2021. The layout in the field used a factorial RAK design with 9 treatment combinations repeated 3 x. Type of Organic Fertilizer: cow manure organic fertilizer, chicken manure organic fertilizer, biofertilizer. Dosage of organic fertilizer: 200 kg/ha, 400 kg/ha, 600 kg/ha. The heaviest pod weight was achieved in the combination of biofertilizer treatment at the dosage of 400 kg/ha at 89.67 g/plant or 6.97 kg/plot and increased production by 109.31% when compared to cow manure organic fertilizer at the rate of 200 kg/ha.